CINTA DALAM BINGKAI FILSAFAT - Ni Luh Gede Wariati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Love becomes an interesting discussion among philosophers, not a few philosophers who discuss love in his thinking. Plato and Soren Kierkegaard also discussed Love in their philosophy, not only Western philosophy in the history of Chinese philosophy Mo Tsu also introduced Universal Love which was used to replace the attitude of discrimination. Love has a positive meaning and goodness, in Greece itself, love is divided into three namely: Philia, Eros and Agape, where the three terms have different definitions of love. Plato believes that love is beauty and gives birth to beauty. For Mo Tzu universal love is the most beneficial action for the community, by applying universal love people will care for each other and love each other because everyone wants to be treated well and loved.